Global spatially explicit crop water consumption shows an overall increase of 9% for 46 agricultural crops from 2010 to 2020: data and software - Chukalla, A.; Mekonnen, M.; Gunathilake, Dahami; Wolkeba, F. T.; Gunasekara, Bhawani; Vanham, Davy (2025)
This dataset comprises spatial and temporal data related to our analysis on blue and green water consumption (WC) of global crop production in high spatial resolution (5 arc-minutes – approximately 10 km at the equator) for the years 2020, 2010 and 2000.